GP144 Quality of life and the impact of caring for a child with prader willi syndrome. (June 2019) - Meade, Christina; Martin, Ruth; Lyons, Jacqueline; McCrann, Ann; Roche, Edna
Abstract : Aims: To evaluate the family impact of caring for a child with Prader Willi Syndrome (PWS), the caregiver burden and the parents perceived impact on the affected child's Quality of Life (QOL). Methods: All children diagnosed with PWS, attending the service were invited to participate (n=44). QOL was evaluated using the PedsQL questionnaire. The Family Impact module was used to measure the impact of PWS on the family unit. Parent Proxy Reports were used to evaluate the parent's perception of the child's QOL. The PWS Burden questionnaire was used to assess additional challenges associated with managing a child with PWS. Results: Participants included nineteen children. Median age was 7.9 years (range 0.6 years – 18.1 years). Majority were female (n=14, 74%). Median age at diagnosis was 2.5 weeks (range birth – 2.7 years). Growth Hormone treatment was in place for the majority (n=14, 74%) commenced at median age of 2.6 years. Of the reporting parents, 89% (n=17) were mothers, 37% (n=7) reported to be homemakers. All children were living in 2 parent households. QOL family impact: Families reported 'Worry' about medical treatment, the future, others reactions to their child's condition and impact on other family members as impacting most significantly on the family. Significant negative correlations between family QOL and age/weight were observed across many domains, the strongest apparent in the area of family functioning and family relationships. QOL parent proxy reports: PWS was perceived by parents to impact most significantly on their child's School functioning. Significant negative correlations with age and weight were observed. Parents identified psychosocial health and social functioning to be most notably affected. Burden: Various areas were identified as significantly adding to caregiver burden such as concerns regarding long-term health and disruptions to family routines. Conclusion: PWS impacts significantly on QOL for the affected child and the entire family.